Produksi Dan Kualitas Jerami Padi Sumber Hijauan Pakan Dengan Waktu Panen Dan Dosis Pupuk Berbeda : Production and Quality of Rice Straw as Forage Sources with Different Harvest Time and Fertilizer Doses - Radian Syafiyullah; N R Kumalasari; L Abdullah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
This study was aimed to analyze the fertilizer dosage and harvest age in Ciherang rice varieties to increase the rice straw production and quality. This study used a block randomized design with 3 x 4 blocks divided based on harvest age H1 = 114 days, H2 = 118 days and H3 = 122 days. The treatment was fertilizer dose level which consists of 4 levels, namely: P0 (control) = Urea 55 g+SP-36 5 g+KCl 6 g, P1= Urea 63,25 g+SP-36 5 g+KCl 6 g, P2= Urea 71,50 g+SP-36 5 g+KCl 6 g dan P3= Urea 79,75 g+SP-36 5 g+KCl 6 g. The variables observed were straw production, grain production, filled grain production, empty grain production, crude protein (CP), crude fiber (CF), Acid Detergent Fiber (ADF) and Neutral Detergent Fiber (NDF). Data were analyzed using analysis of variance followed by Duncan's Multiple Range Test. The results showed that P3 was significantly (p< 0.05) the highest among fertilizer dose level treatments on the straw production (27.63 tons ha-1), filled grain production (5.52 tons ha-1), and reduced empty grain (0.15 tons ha-1). The Quality of rice straw were CP 7.49%, CF 20.35%, ADF 55.03 %). While at harvest age, H1 was significantly (p< 0.05) the highest among harvest ages treatments on the variables of straw production 28.18%, empty grain production 0.21 tons ha-1) and NDF 69.11%. It can be concluded that the best fertilizer dosage was an addition of urea by 45% with harvesting age of 114 days. Key words: fertilizer, harvest age, production, quality, rice straw